Crop systems and cover crops for soybean production in the Cerrado (Research, Society and Development, 2022)
The objective of the present work was to evaluate the effect of different cover crops on the agronomic and yield characteristics of soybean under no-tillage and conventional cropping systems. The experiment was carried out in an experimental area in the municipality of Monte Carmelo-MG, experimental agricultural years 2016/2017 and 2018/2019, using a randomized block design, with four replications, in a strip scheme. The treatments consisted of six species of plants for ground cover (2016/2017 was sown sunn hemp, pigeon pea, lab lab, millet, sorghum and fallow and 2018/2019 were sunn hemp, forage radish, pigeon pea, millet, lab lab and fallow) and by two cropping systems (no-tillage and conventional tillage). The soybean cultivar used was SYN 1562 IPRO*(RR) in 2016/2017 and NS 7667 (Ipro, Nidera) in 2018/2019. In soybean cultivars, heights of heights: heights the final agronomic characteristics, of the first soybean, of the first plants, number of seeds per pod and plant soybean yield. The highest heights of soybean plants were after the cultivation of sunn hemp, pigeon pea, lab lab and fallow. The height of the first wave was higher over sunn hemp straw, lab lab and fallow and millet. The use of millet, forage radish and pigeon pea will provide more pods per plant in number cultivated. In 2016/2017 the no-tillage system increased soybean productivity. In the planting system all cover crops will provide conventional yield increase in 2018/2019.